2016
DOI: 10.1007/s11160-015-9417-7
|View full text |Cite
|
Sign up to set email alerts
|

An unlikely partnership: fishers’ participation in a small-scale fishery data collection program in the Timor Sea

Abstract: Traditional fisheries stock assessment methods and fishery independent surveys are costly and time consuming exercises. However fishers trained in data collection and utilising other skills can reduce costs and improve fishery assessments and management. A data collection program was conducted by Australian and Indonesian scientists with small-scale Indonesian sea cucumber fishers to evaluate the approach and then capture its benefits. The data fishers recorded allowed for the first stock assessment of this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…An ethnobiology is one of potential approach to strengthen local wisdom using scientific method, it will ensure an effective and efficient fisheries management based on community initiative (Oktaviani et al, 2016). Prescott et al (2016) found that a strong engagement with fishers has benefit for effective monitoring of the resources. It also realized the hidden and valuable information from the fishers to the fisheries that enriched the scientific findings and minimize the uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…An ethnobiology is one of potential approach to strengthen local wisdom using scientific method, it will ensure an effective and efficient fisheries management based on community initiative (Oktaviani et al, 2016). Prescott et al (2016) found that a strong engagement with fishers has benefit for effective monitoring of the resources. It also realized the hidden and valuable information from the fishers to the fisheries that enriched the scientific findings and minimize the uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Fishers viewed annual decreases to their total allowable catch as putative and unnecessary, leading to controversy and feelings of distrust between fishery stakeholders (Verweij et al., ). Feedback, communication and agreed‐upon standards for information use and processing may alleviate some of the conflict that can arise as a result of differences in perception and/or interpretation of data (Prescott et al., ; Verweij et al., ), but perception differences may persist.…”
Section: Looking To the Future: A Transdisciplinary Approach For Highmentioning
confidence: 99%
“…Feedback, communication and agreed-upon standards for information use and processing may alleviate some of the conflict that can arise as a result of differences in perception and/or interpretation of data (Prescott et al, 2016;Verweij et al, 2010), but perception differences may persist.…”
Section: Unintended Consequences and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IEK and SK were used to help Indigenous Nyul Nyul rangers respond to threats to the health of wetlands and to monitor their condition. Prescott et al (2016) describe a collaborative research project with traditional Indonesian fishers of trepang around Scott Reef in north-western Australia. This project worked with fishers who provided catch data that facilitated more accurate monitoring than data collected independently of the fishers.…”
Section: A Meeting To Foster Relationships and Understandingmentioning
confidence: 99%